Unique promotional strategy for sustainability of community based tourism (CBT) - Joydeep Mukherjee; Sharmistha Banerjee (International Journal of Technology for Business (IJTB), 2019)
Community based tourism (CBT) focuses on the protection of socio-cultural values and economic benefits of stakeholder host communities of tourism destinations. It is increasingly being promoted as an avenue of sustainable tourism development. But for achieving economic sustainability in long run for CBT initiatives it is imperative to ensure revenue generation through regular tourist footfall and productive use of available resources. The purpose of the study is to examine the tourists' awareness level about CBT initiatives. The paper also seeks to analyze how far the aware tourist is able to contribute to economic sustainability of CBT destinations. It also aims to identify popular tourist information dissemination sources so that a policy prescription can be suggested for effective marketing and promotion strategy of CBT. The study used questionnaire based survey method and collected primary data of 100 domestic tourists focusing on the CBT destinations of Northern part of west Bengal region. Statistical analysis is used to develop a framework to explain the theoretical relationship of CBT awareness level and tourists' visit possibility. The findings will lead to policy prescriptions for CBT developers to achieve sustainability in long run by developing unique promotional strategy to increase tourist visit.
Keywords: 650; Community based tourism; Sustainability; Promotion; CBT Awareness; Visit Willingness